Pengembangan Aplikasi Anola Berbasis Android untuk Pembelajaran Atletik Nomor Lari Jarak Pendek - Bambang Hariyanto (Jurnal Didaktika Pendidikan Dasar, 2020)
The product of the digital age advances is the existence of sophisticated devices such as smartphones, which are now an inseparable part of human life. This device makes all human activities become practical and fast. The development of the Athletics application Running Number abbreviated as ANOLA is one of the learning innovations. The purpose of this study is to describe the application development, practicality and effectiveness of android-based so that it can be used as a learning media for athletic material running number Method used is Design and Development (D & D) while the process of developing an ANOLA application uses the Analysys, Design, Development, Implementation, Implementation, Evaluation (ADDIE). The results of the study show that the practicality of ANOLA application shows the number 94.67% (Very Practical), while the effectiveness test is 96% (Very Effective). Feasibility test by media experts obtained 96.67% (Very Eligible). The results of the competency test through pre-test and post-test showed an increase in mastery learning in class 8 D students by 53% in the realm of knowledge (KI.3) and by 23% in the realm of skills (KI. 4).